ANALISIS PENGARUH SOSIALISASI INVESTASI OLEH PERUSAHAAN PERUSAHAAN SEKURITAS TERHADAP MINAT CALON INVESTOR DALAM BERINVESTASI DI BIDANG EFEK MELALUI REKSA DANA - Sinaga, Kepler; Dakhi, Restui (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2023)
This research aims to analyze whether or not there is an influence of Investment Socialization by Securities Companies on the Interest of Potential Investors in Investing in Securities through mutual funds. The formulation of the problem in this research is whether there is an influence of investment socialization on the interest of potential investors, where the population of this study is 7,088 people with a sample size of 98 people selected using the Slovin formula. Based on the results of hypothesis testing, it can be concluded that the significance value of the t-test X1 = 0.014 <0.05; X2 = 0.040<0.05; X3 =0.091>0.05; X4 = 0.570>0.05 and X5 = 0.000<0.05 (df = 0.05/2; n-k-1) where X1, Ha4 was rejected. The results of the F-test obtained a significance value of Fcount of 0.000<0.05 (k; n-k) which means Ha was accepted and Ho was rejected or Investment Socialization (X1 Meanwhile, the detrending coefficient (R Square) shows that the Interest of Potential Investors is influenced by Investment Socialization by 62.1% and the remaining 37.9% is influenced by other factors not examined in this research. The results of the multiple linear regression analysis obtained an equation, namely Y = 9.468 + 0.616x1 + 0.525x2 + 0.373x3 + 0.126x4 + 0.793x5. Suggestions given to securities companies to increase the frequency of investment outreach to the public, especially students, with more emphasis on classifying the types of risks and benefits of investment to encourage public or student participation in the Capital Market